Islam sebagai Agama dan Peradaban - Qosim Nursheha Dzulhadi (Universitas Darussalam Gontor, 2015)
Islam and civilization can not be separated. Since its presence, Islam has brought the concept and mission of civilization that is inherent in it. Islamic civilization sourced from dîn (religion) which came from the revelation of Allah. That is why the civilization well known as tamaddun or madaniyyah, because it comes from that dîn . Then the high expression tamaddun Islam in the history of human civilization got its place in Yathrib wich later turned into Medina. So, Medina is the place where tamaddun was proclaimed to the whole world as described by Syed Muhammad Naquib al-Attas. And madaniyyah, according to Muhammad ‘Abduh is more appropriately used to refer to Islamic civilization, because the spiritual aroma-religion (al-dîn) is more pronounced and prominent. Departing from this, this article will break down the details of the meaning and concept of civilization, in which the comparison will be made between the concepts of Western civilization with Islamic civilization.This is necessary in order to provide a clearer distinction of the two concepts of civilization.This article will also review the nature of Islam as dîn and tamaddun-madaniyyah with based on the views of the two great Muslim thinkers, Muhammad ‘Abduh and Syed Muhammad Naquib al-Attas. In addition will include also a critique of modern Western civilization, which is currently hegemonic civilization.